Intervention as a social practice: knowledge formation and transfer in the everyday of police missions. Issue 2 (14th March 2016) - Distler, Werner
ABSTRACT: The problematic nature of biased knowledge held by professionalized experts and aid workers in statebuilding is already recognized. Yet we still lack understanding on knowledge formation and transfer in the everyday of statebuilding operations. I argue that the actors on the ground gain their knowledge in powerful and self-referential socialization processes. The aim of this article is to reconstruct via an interactionist theoretical framework, how German police officers, deployed for a maximum of 12 months, perceive and interpret other actors and their mission in Kosovo, how they gain this knowledge and how it relates to their work. I draw two conclusions: first, the police officers, both experienced and newcomers, share mostly negative attitudes towards local actors and the mission. Second, the most important mode of knowledge formation and transfer behind these similar attitudes is the informal interaction with experienced interveners and local actors, not official trainings or information. These informal modes of knowledge transfer have a limiting effect on the practice of statebuilding. New knowledge is difficult to gain in short-term deployment, instead stereotypes are reaffirmed. Interveners are not independent units and the social practice of an operation cannot simply be planned; it develops on the ground in specific forms.